Peculiarities of microvasculature condition in patients with traumatic brain injury consequences - Салій, Зоя Василівна (ScienceRise: Medical Science, 2016)
The aim of the given research was to analyze peculiarities of microvasculature condition in patients with traumatic brain injury (TBI) consequences and to determine its influence on traumatic brain disease course. Methods. The assessment of the microvasculature structural characteristics (total capillary length; the arterial and venous links length, caliber, tortuosity factor and tone; perivascular edema value) was carried out in 103 patients with TBI consequences using capillaroscopy method with Angio Pro software. Neurological status was evaluated by Neurological Outcome Scale for Traumatic Brain Injury (NOS-TBI), cognitive condition – by Montreal Cognitive Assessment (MoCA), level of anxiety and depression – by HADS scale. The percentage of peripheral blood leukocytes in the apoptosis (АnV+) and necrosis (РІ+) stages, as well as reactive oxygen species (ROS+) level were studied using flow cytometry method. Results. Increased tortuosity coefficient of arterioles and venules, increased arteriolar tone, and a tendency for venules lumen to expand with formation of venous stasis phenomena and moderately pronounced signs of perivascular edema were diagnosed in patients with different severity of TBI consequences. The relationship between morphological and clinical parameters intensified in older age groups. Thus, in adult patients the cognitive functioning level (by MoCA test) depended on the capillary total length (r=0,416, р=0,002), and tortuosity coefficient of arterioles was higher under conditions of progressing disease (r=0,301, р=0,027) and several syndromes combination in the clinical picture (r=0,317, р=0,019). Conclusion. Stagnant microcirculation type with moderate perivascular edema signs formation is inherent in patients with TBI consequences. ROS+ concentration increasing adversely affected the capillary length and contributed to perivascular edema growth. The share of leukocytes in necrosis and apoptosis stages correlated moderately with tortuosity coefficient of arterioles and venules